Perception of Stakeholders on Forest Governance under JFM:A Case Study from Odisha - Sinha, B. K. P.; Behera, Minaketan (Indian Forester, 2016)
Forest governance is an important factor for poverty eradication and sustainable forest management. A field study was conducted to understand the parameters of governance in four different JFM implemented models (FDA, OFSDP, UJFM and RLTAP) in four forest division of Odisha. The data were collected from VSS members, forest personals, PRI members and civil society (NGOs) to identify and establish building blocks of forest governance. The parameters of Forest Governance covered are based on the Good Forest Governance Framework. The finding of the study revealed that maximum gap was observed in livelihood sustainability followed by transparency, democratization and accountability. The achievement in totality accounts for 77 per cent with corresponding gap of 23 per cent in overall forest governance. Among the four JFM models under study OFSDP was found to be the best available JFM model suiting to condition of the State of Odisha and fulfilling the requirements of forest dependents.